Negotiating professional learning relationships in the cross-cultural school improvement context of Abu Dhabi, UAE - Govender, Thiloshnee (Curtin University, 2019)
This study uses hermeneutic phenomenology to explore the uniquely-lived experiences of Western education advisors who lead teachers’ professional learning through mentoring in the cross-cultural school improvement context of Abu Dhabi, UAE. It specifically examines those dynamics that support or hinder the efficacy of education advisors, revealing the complexities of working in cross-cultural mentoring relationships. The findings, represented in a framework of cross-cultural mentoring interactions, indicate powerful connections between the elements of person, culture and context.